2000
DOI: 10.1159/000025466
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Changes in Interferon-γ and Interleukin-4 Secretion by Purified Human CD4+ and CD8+ T Cells

Abstract: Aging is associated with a decline in immune function. Interferon-γ (IFN-γ) and interleukin-4 (IL-4), two important immune deviation-related cytokines, are mainly produced by type 1 and type 2 T cells, respectively. To investigate the age-associated changes in the secretion of these two cytokines, 20 elderly and 20 young subjects fulfilling the SENIEUR protocol were enrolled. The ratios of CD4+ to CD8+ T cells were not different between the two age groups. The CD4+ and CD8+ T cells were purified by a magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
4
16
1
1
Order By: Relevance
“…The role of interferons in aging is not yet clear. Decreased levels of interferons (IFN-a and -g (Miller, 1980;Lio et al, 2000)) were found by some laboratories while other investigators determined increased levels (Fahey et al, 2000;Sakata-Kaneko et al, 2000;Yen et al, 2000). In addition, our data are in concordance with the latter showing that activated T cells of both subsets from elderly individuals produced more IFNg than from young controls.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The role of interferons in aging is not yet clear. Decreased levels of interferons (IFN-a and -g (Miller, 1980;Lio et al, 2000)) were found by some laboratories while other investigators determined increased levels (Fahey et al, 2000;Sakata-Kaneko et al, 2000;Yen et al, 2000). In addition, our data are in concordance with the latter showing that activated T cells of both subsets from elderly individuals produced more IFNg than from young controls.…”
Section: Discussionsupporting
confidence: 90%
“…Unprimed cells carry the CD45RA isoform of the CD45-receptor, while memory cells express the CD45R0 epitope (Vitetta et al, 1991). We and others (O'Leary et al, 1988;Yen et al, 2000) found no significant changes of the CD4/ CD8 ratio with aging. This is an interesting fact as some neurological disorders (DAT and MS, for instance) show increased CD4/CD8-ratios (Shalit et al, 1995;Crucian et al, 1995b;Schindowski et al, 1999).…”
Section: Discussioncontrasting
confidence: 38%
“…Previous studies demonstrated that a helminth infection-induced Th2 immune response is protective in murine models of inflammatory diseases, including inflammatory bowel disease [20] and Type 1 diabetes [15]. Several studies in humans [22,26] Our previous data demonstrated that Th2 cytokine elevation by Hp infection in the small intestine was blocked by anti-CD4 antibody [16]. Therefore, a decrease in the number of CD4 + cells might be one of the reasons for the decline in Th2 cytokine expression in 18 M mice.…”
mentioning
confidence: 99%
“…For these reasons, we believe that variation in ACT score is not reflected by variation in age in the present study. In terms of cytokine profiles in CD4 + T-cells, it has been shown in healthy subjects in three different age groups (21-31 years, 80-81 years and 100-103 years) that the ratio between type-2 cytokines and type-1 cytokines is unaffected by age [43]. Although age-related changes of the immune function in human asthma are yet to be studied in detail, there are studies in animal models and humans suggesting that age can affect both innate and adaptive immune responses [39].…”
Section: Figurementioning
confidence: 99%